2000
DOI: 10.1177/009102600002900203
|View full text |Cite
|
Sign up to set email alerts
|

Internal Politics in Public Administration Systems

Abstract: Politics is one of the most common yet least studied phenomena in organizations. This study examines employees' perceptions of organizational politics in the public sector and suggests that it mediates the relationship between job congruence (e.g., person-organization fit and level of met-expectations) and employee performance (e.g., organizational citizenship behavior [OCB] and in-role performance). A survey was conducted among 303 individuals in public personnel from two local municipalities in the north of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(17 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Although a few studies have found perceptions of organizational politics to predict OCB (Vigoda, 2000a;Witt et al, 2002), others have found no relationship between the two variables (Aryee et al, 2004;Cropanzano et al, 1997). Perhaps, the effect of perceptions of organizational politics on OCB-related behaviors such as helping coworkers is indirect rather than direct.…”
Section: Trust and Helpingmentioning
confidence: 99%
“…Although a few studies have found perceptions of organizational politics to predict OCB (Vigoda, 2000a;Witt et al, 2002), others have found no relationship between the two variables (Aryee et al, 2004;Cropanzano et al, 1997). Perhaps, the effect of perceptions of organizational politics on OCB-related behaviors such as helping coworkers is indirect rather than direct.…”
Section: Trust and Helpingmentioning
confidence: 99%
“…In most employment contexts, however, OCB is still regarded as a set of individual behaviors that employers deem desirable (Vigoda, 2000). Cultivating and predicting these behaviors has become an important focus for both practitioners and scholars.…”
Section: Emergent Themes From the Literaturementioning
confidence: 99%
“…. enhance organizational effectiveness” (Vigoda, 2000, p. 191). Within the literature on OCB, many scholars distinguish between organizational citizenship behavior directed at individuals (OCBI) and organizational citizenship behavior directed at organizations (OCBO; Williams & Anderson, 1991).…”
Section: Outcome Measuresmentioning
confidence: 99%